Transcriptome Analysis of Circulating Immune Cell Subsets Highlight the Role of Monocytes in Zaire Ebola Virus Makona Pathogenesis - Menicucci, Andrea R.; Versteeg, Krista; Woolsey, Courtney; Mire, Chad E.; Geisbert, Joan B.; Cross, Robert W.; Agans, Krystle N.; Jankeel, Allen; Geisbert, Thomas W.; Messaoudi, Ilhem (Frontiers in Immunology, 2017)
Existing models of Ebola virus disease (EVD) suggest antigen-presenting cells (APCs) are initial targets of Zaire ebolavirus (ZEBOV). In vitro studies have shown that ZEBOV infection of monocytes and macrophages results in the production of inflammatory mediators, which may cause lymphocyte apoptosis. However, these findings have not been corroborated by in vivo studies. In this study, we report the first longitudinal analysis of transcriptional changes in purified monocytes, T-cells, and B-cells isolated from cynomolgus macaques following infection with ZEBOV-Makona. Our data reveal monocytes as one of the major immune cell subsets that supports ZEBOV replication in vivo. In addition, we report a marked increase in the transcription of genes involved in inflammation, coagulation, and vascular disease within monocytes, suggesting that monocytes contribute to EVD manifestations. Further, genes important for antigen presentation and regulation of immunity were downregulated, potentially subverting development of adaptive immunity. In contrast, lymphocytes, which do not support ZEBOV replication, showed transcriptional changes limited to a small number of interferon-stimulated genes (ISGs) and a failure to upregulate genes associated with an antiviral effector immune response. Collectively, these data suggest that ZEBOV-infected monocytes play a significant role in ZEBOV-Makona pathogenesis and strategies to suppress virus replication or modify innate responses to infection in these cells should be a priority for therapeutic intervention.